Pertuzumab and Erlotinib in Patients With Relapsed Non-Small Cell Lung Cancer: A Phase II Study Using 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Imaging. (23rd January 2014) - Hughes, Brett; Mileshkin, Linda; Townley, Peter; Gitlitz, Barbara; Eaton, Keith; Mitchell, Paul; Hicks, Rodney; Wood, Katie; Amler, Lucas; Fine, Bernard M.; Loecke, David; Pirzkall, Andrea
Abstract: Author Summary: Background: Combination blockade of human epidermal growth factor receptor (HER) family signaling may confer enhanced antitumor activity than single-agent blockade. We performed a single-arm study of pertuzumab, a monoclonal antibody that inhibits HER2 dimerization, and erlotinib in relapsed non-small cell lung cancer (NSCLC). Methods: Patients received pertuzumab (840-mg loading dose and 420-mg maintenance intravenously every 3 weeks) and erlotinib (150-mg or 100-mg dose orally, daily). The primary endpoint was response rate (RR) by 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) at day 56 in all patients and those with EGFR wild-type tumors. Results: Of 41 patients, 28 (68.3%) experienced treatment-related grade ≥3 adverse events, including pneumatosis intestinalis (3 patients), resulting in early cessation of enrollment. Tissue samples from 32 patients showed mutated EGFR status in 9 of 41 (22%) and wild-type EGFR in 23 of 41 (56%). The FDG-PET RR for patients with assessments at day 56 was 19.5% in all patients ( n = 41) and 8.7% in patients with wild-type EGFR NSCLC ( n = 23). Investigator-assessed computed tomography RR at day 56 was 12.2%. Conclusion: FDG-PET suggests that pertuzumab plus erlotinib is an active combination, but combination therapy was poorly tolerated, which limits its clinical applicability. More research is warranted to identify drug combinations that disrupt HER receptor signaling but that exhibit improved tolerability profiles.